2010
DOI: 10.1007/s10562-010-0391-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesostructured or Alumina-mesostructured Silica SBA-16 as Potential Support for NOx Reduction and Ethanol Oxidation

Abstract: 59-3 FIELD Section Title:Air Pollution and Industrial Hygiene 49, 51, 67 Faculte des sciences II, Laboratoire de Chimie Physique des Materiaux (LCPM), Campus Fanar, Universite Libanaise, Jdeideh, Lebanon. FIELD URL: written in EnglishSynthesis of some meso-structured SiO2 or aluminosilica (SBA-16 and Al-SBA-16) with a 3-dimensional cubic structure is reported. Structural and porosity properties of these materials were studied by x-ray diffraction, N2 sorption, and transmission electron microscopy imaging.; Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…on Brönsted acid sites and bands at 1455 and 1620 cm -1 are assigned to pyridine coordinatively adsorbed on Lewis acid sites (PyL) [37]. The peak at 1490 cm -1 is due to interaction of pyridine with both Brönsted and Lewis acid sites [25]. The bands appear at 1444 and 1595 cm -1 are related to physisorbed pyridine, which completely disappear after outgassing at 200°C, indicating that only chemisorbed pyridine remain on the surface of SBA-16.…”
Section: Textural Properties and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…on Brönsted acid sites and bands at 1455 and 1620 cm -1 are assigned to pyridine coordinatively adsorbed on Lewis acid sites (PyL) [37]. The peak at 1490 cm -1 is due to interaction of pyridine with both Brönsted and Lewis acid sites [25]. The bands appear at 1444 and 1595 cm -1 are related to physisorbed pyridine, which completely disappear after outgassing at 200°C, indicating that only chemisorbed pyridine remain on the surface of SBA-16.…”
Section: Textural Properties and Characterizationmentioning
confidence: 99%
“…Similarly, a recent report by Costa et al demonstrated the synthesis of mesostructured silica or alumina-mesostructure silica SBA-16 using direct method. But the incorporation of alumina into SBA-16 leads to a structure with poor order and low BET surface area [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the natural adsorbents, such as wheat straw, coconut coir pith, tree fern, etc., demonstrated a low mechanic resistance to abrasive forces, low loading capacities, and relatively weak interactions with heavy metal cations [7][8][9]. To overcome these drawbacks, recent studies are focused on the use as adsorbents the mesoporous silica materials, such as MCM-41 [10,11], SBA-15 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and SBA-16 [30][31][32][33][34][35][36] due to their ordered mesoporous structure with high surface area and appropriate pore size for the accommodation of guest molecules [37]. Notwithstanding, as the pure siliceous materials have only silanol groups on their surface, it is necessary to create specific binding sites by functionalization of the adsorbent surface with chemically bonded groups, such as -SH [15][16][17], -COOH [14,17], and -NH 2 [4,10,12,[19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, as the pure siliceous materials have only silanol groups on their surface, it is necessary to create specific binding sites by functionalization of the adsorbent surface with chemically bonded groups, such as -SH [15][16][17], -COOH [14,17], and -NH 2 [4,10,12,[19][20][21][22][23][24]. In particular, the effect of amine functionalization of SBA-15 and SBA-16 has been extensively studied for removal of metal ions from various sources [12,[19][20][21][22][23][24][27][28][29][30][31][32][33][34][35][36], or controlled drug release [25,26,37] because of easy accommodation of the aminopropyl groups in the ordered pore structure of SBA-15 adsorbent and the efficient van der Waals electrostatic interaction of amino groups with Pb 2+ upon optimized adsorption conditions, as it was confirmed by us previously [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation